Assessing the Impact of a Winter Storm on the Beach and Dune Systems and Erosion Mitigation by Plants - Maximiliano-Cordova, Carmelo; Martínez, M. Luisa; Silva, Rodolfo; Hesp, Patrick A.; Guevara, Roger; Landgrave, Rosario (Frontiers in Marine Science, 2021)
The impact of storms on coastal dunes and beaches and the effects they induce in topography and plant communities are natural processes that contribute to maintaining natural coastal dynamics. However, because coasts are often densely populated, these phenomena are perceived as major threats to human property. To protect human assets sustainably, nature-based defenses have emerged as an option. Coastal dunes act as natural buffers that mitigate the extent of erosion and inland flooding, and their resistance depends on the biogeomorphological feedback between the plants and the dunes. This study aimed to evaluate the effect of one winter storm on beach and dune topography and the plant communities, and to explore the effect of plants in mitigating erosion on beaches with different geomorphological features. The effects on plant communities were evaluated by comparing diversity and plant cover before and after the storm. Later, the role of plants in conferring dune resistance against erosion was examined by measuring erosion on the exposed face of the dunes considering plant cover and plant richness. The results did not show significant differences in plant diversity and plant cover between pre-and post-storm conditions, but turnover of species was recorded. The dune building species were not affected but inland species disappeared. Erosion was reduced when the dunes were higher and, furthermore, plant cover was negatively correlated with erosion on these dunes. The results showed a reduced impact of the storm on the plant communities, which is important as it facilitates the recovery of dunes by the dune-building species and protects them in a subsequent storm. The novelty of this study is that: a) it demonstrates the species-specific role of plants in mitigating dune erosion in field conditions; b) it shows the interaction between plant-related features and geomorphological variables in promoting dune resistance to erosions, and c) it explores the immediate effect of a winter storm on the plant community and dune-building species.